Long-term prenatal stress increases susceptibility of N-methyl-D-aspartic acid-induced spasms in infant rats - Hyeok Hee Kwon; Taekwan Lee; Jinpyo Hong; Dong Woon Kim; Joon Won Kang (Korean Pediatric Society, 2018)
PurposeInfantile spasms, also known as West syndrome, is an age-specific epileptic seizure. Most patients with this condition also exhibit delayed development. This study aimed to determine the effect of long-term prenatal stress on susceptibility to infantile spasms.MethodsWe subjected pregnant rats to acute or chronic immobilization stress. Resulting offspring received N-methyl-D-aspartic acid (15 mg/kg, intraperitoneally) on postnatal day 15, and their behaviors were observed 75 minutes after injection. The expression of KCC2 and GAD67 was also determined using immunohistochemistry.ResultsExposure to long-term prenatal stress increased the frequency of spasms and decreased the latency to onset of spasms compared with offspring exposed to short-term prenatal stress. Expression of KCC2 and GAD67 also decreased in the group exposed to long-term prenatal stress compared with the group exposed to short-term prenatal stress.ConclusionOur study suggests that exposure to long-term prenatal stress results in increased susceptibility to seizures.